1998
DOI: 10.3989/tp.1998.v55.i2.308
|View full text |Cite
|
Sign up to set email alerts
|

Paléoenvironment durant le Pleistocene Supérieur en Vaucluse: analyse palynologique des couches inférieures de l´abri de la Combette (Bonnieux, Vaucluse, France)

Abstract: RESUMEL'étude palynologique de l'abri de La Combette nous informe sur l'évolution de la végétation autour du site pendant le Pleistocene supérieur, au Würm ancien (début du stade isotopique 3). Les différentes phases climatiques mises en évidence sont caractérisées par la dominance du pin sylvestre et la présence notable d'espèces méditerranéennes. On constate le caractère refuge du site. RESUMENEl estudio palinologic o del Abrigo de La Combette nos informa sobre la evolución seguida por la vegetación en el El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Polygonal wedge networks caused by ground thermal contraction and filled with windblown sand (sand wedges) were also described (Bouteyre and Allemann, 1964;Gabert-Delay, 1967;Cailleux and Rousset, 1968;Nury and Roux, 1969;Arnal, 1971aArnal, , 1971b. Windblown sand also contributed to the infilling of karst cavities (Brochier and Livache, 1978;Debard, 1987Debard, , 1988Lopez Saez and Texier, 1998;Texier et al, 2003;Saos et al, 2014;Puaud et al, 2015). The main conclusions that can be drawn from these works are as follows:…”
Section: Regional Setting 21 Geological and Geomorphological Settingmentioning
confidence: 90%
“…Polygonal wedge networks caused by ground thermal contraction and filled with windblown sand (sand wedges) were also described (Bouteyre and Allemann, 1964;Gabert-Delay, 1967;Cailleux and Rousset, 1968;Nury and Roux, 1969;Arnal, 1971aArnal, , 1971b. Windblown sand also contributed to the infilling of karst cavities (Brochier and Livache, 1978;Debard, 1987Debard, , 1988Lopez Saez and Texier, 1998;Texier et al, 2003;Saos et al, 2014;Puaud et al, 2015). The main conclusions that can be drawn from these works are as follows:…”
Section: Regional Setting 21 Geological and Geomorphological Settingmentioning
confidence: 90%
“…This interval, may or may not render the exact Mousterian occupation period. In the absence of other datable assemblages, the data do not exclude the possibility that the site was used before the MIS 5a, although that appears to be an unlikely scenario (see also data in López-Sáez et al 1998). Chronostratigraphic, sedimentological and palaeoclimatological comparisons to local-to-regional sedimentary archives proposed by Mologni et al (in press) suggests a slightly earlier infilling of the rock-shelter during MIS 5b/5a.…”
mentioning
confidence: 78%
“…Secondary loess ("loess-like" sediments) dominates the upper series, encompassing the layers: 3) D; 4) B/C; and 5) A, on top of the "Mousterian living floor" (Texier et al 2003: 81). The palynological study by López-Sáez et al (1998), below level F/G, revealed three palynological phases matching Würm glaciation (MIS 5d to MIS 2; cf. Ehlers et al 2011) Mologni (2017) and Mologni et al (in press) added a sedimentological and micromorphological study to understand better the sedimentary formation processes of the sequence and the related environmental conditions.…”
Section: In Conjunction Withmentioning
confidence: 99%
“…Il est également fréquent de rencontrer au niveau des gorges, combes et cluses les plus encaissées, des baumes ou « abris sous roche », formes d'érosion témoignant de la vigueur des processus périglaciaires pléistocènes. (Cattani & Renault-Miskovsky, 1989 ;Magnin, 1991 ;López-Sáez et al, 1998 ;Théry, 1998), ces valeurs ne sont pas considérablement éloignées de celles obtenues en rhexistasie sur des lithologies marno-calcaires et topographies voisines du Luberon (Delannoy & Rovéra, 1996 ;Hallet et al, 1996 ;Lecompte et al, 1998 ;Rovéra et al, 1999). Ces vitesses d'érosion, sans être exceptionnelles, sont aussi très comparables à celles obtenues en basse Provence sur de plus longues durées, dans des travaux intégrant également l'évolution de la tectonique active (Siame et al, 2004 ;Molliex et al, 2013).…”
Section: -Les Formes Et Formations Pléisto-cènes Du Grand Luberonunclassified